Optimization of Ultrasonic Assisted Extraction Process on Antioxidant Activity of Honje Fruit Extract (Etlingera elatior) Using Surface Response Method - Artta Gracia Malau; Asri Widyasanti; Selly Harnesa Putri (Syarif Hidayatullah State Islamic University, 2021)
Honje fruit (Etlingera elatior) contains bioactive compounds as antioxidants. An antioxidant can be obtained by extraction. This research aimed to determine the best combination of solvent amount and extraction time to produce the optimal yield and antioxidant activity. The extraction method was UAE (Ultrasound Assisted Extraction) using ethanol 96% solvent amount 125 mL to 250 mL and time level of 30 to 60 minutes. The RSM (Response Surface Methodology) in the Design Expert 11 application was used to arrange the extraction combination treatment, which resulted in 13 runs. Parameters analyzed were total yield, antioxidant activity, pH, specific gravity, and color. The results showed that total yield was revealed quadratic, Y1 = 19.05 – 1.76A + 0.32B – 0.002AB + 0.023A2 – 0.0005B2 and the antioxidant activity was revealed linear, Y2 = 408.147 – 6.424A + 0.326B. The optimum treatment was achieved in the amount of solvent 174.815 ml and extraction time of 60 minutes resulted in a total yield of 17.125% and antioxidant activity of 77.55 ppm that could be classified as strong.